Valorization of Marine Waste: Use of Industrial By-Products and Beach Wrack Towards the Production of High Added-Value Products - Rudovica, Vita; Rotter, Ana; Gaudêncio, Susana P.; Novoveská, Lucie; Akgül, Füsun; Akslen-Hoel, Linn Kristin; Alexandrino, Diogo A. M.; Anne, Olga; Arbidans, Lauris; Atanassova, Miroslava; Bełdowska, Magdalena; Bełdowski, Jacek; et al. (Frontiers in Marine Science, 2021)
Biomass is defined as organic matter from living organisms represented in all kingdoms. It is recognized to be an excellent source of proteins, polysaccharides and lipids and, as such, embodies a tailored feedstock for new products and processes to apply in green industries. The industrial processes focused on the valorization of terrestrial biomass are well established, but marine sources still represent an untapped resource. Oceans and seas occupy over 70% of the Earth’s surface and are used intensively in worldwide economies through the fishery industry, as logistical routes, for mining of ores and exploitation of fossil fuels, among others. All these activities produce waste. The other source of unused biomass derives from the beach wrack or washed-ashore organic material, especially in highly eutrophicated marine ecosystems. The development of high-added-value products from these side streams has been given priority in recent years due to the detection of a broad range of biopolymers, multiple nutrients and functional compounds that could find applications for human consumption or use in livestock/pet food, pharmaceutical and other industries. This review comprises a broad thematic approach in marine waste valorization, addressing the main achievements in marine biotechnology for advancing the circular economy, ranging from bioremediation applications for pollution treatment to energy and valorization for biomedical applications. It also includes a broad overview of the valorization of side streams in three selected case study areas: Norway, Scotland and the Baltic Sea.